Analysis and suppression of noise in manual gearbox for military equipment based on acoustic finite element simulation - Pan, Tengyue; Shen, Xinmin; Peng, Wenqiang; Zhang, Jiaojiao; Yang, Xiaocui; Jiang, Chengming (Sound & Vibration, 2026)
To improve the acoustic stealth performance of military equipment, it is essential to analyze and suppress the radiation noise of the manual gearbox as a critical unit. Based on a three-dimensional model of a 5-speed synchromesh gearbox and analysis of its operating principle, the vibration characteristics are studied using multibody dynamics. The housing vibration obtained from the multibody simulation is then used as the acoustic boundary condition in a coupled acoustic-structural finite element simulation to compute the sound pressure level (SPL) of the radiated noise. Taking the SPL at microphones placed around the gearbox as the evaluation indicator, parametric analysis of gear level, input speed, and external load is conducted, and the feasibility of noise control using sound absorbing materials is verified. The results show that the SPL of radiated noise differs significantly in both frequency and spatial domains, and that gear level is the major influencing factor. The total average SPLs for the five gear levels are 137.91 dB, 134.11 dB, 131.83 dB, 124.86 dB, and 81.29 dB, respectively. Moreover, the noise suppression effect of the sound absorbing layer has directionality: the total average SPL at microphone positions M01/M09 is reduced from 139.96 dB to 122.75 dB for the third gear, and from 91.68 dB to 74.55 dB for the fifth gear.